Daily field checking list by Walter Rosene, April 8, 1934 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Bird checklist dated April 8, 1934. This checklist was used by Walter Rosene to record birds sighted around Little Wall Lake between 3:00 and 7:00. Plustek--flatbed